Patient-Reported Functional Improvement Following Minimally Invasive Sacroiliac Joint Fusion in a Patient with Chronic Post-Traumatic Pelvic and Low Back Pain: A Case Report - Suresh Srinivasan; Amanpal Nandra; Joseph Pathakamuri; Mohan Raj Palani Selvam; Sina Davari Farid; Praveen Reddy Elmati (medtigo Journal of Medicine, 2026)
Background: Chronic sacroiliac (SI) joint dysfunction accounts for roughly 15-30% of low back pain cases, yet it is often missed clinically, particularly among patients whose pelvic anatomy has already been altered by trauma. Case Presentation: A 52-year-old female with an 18-year history of chronic left-sided SI joint and hip pain following a motor vehicle accident with pelvic fracture, external fixation, and subsequent osteomyelitis, including a prior ipsilateral SI joint fusion that had failed to unite (pseudoarthrosis), failed conservative therapies including physical therapy, pharmacotherapy, and multiple pain interventions. Dual fluoroscopically guided SI joint injections provided >80% pain relief, supporting the diagnosis. The patient underwent minimally invasive revision posterior oblique SI joint fusion using the TransLoc screw system. This case also highlights the importance of careful patient selection, diagnostic confirmation, and individualized surgical planning when treating SI joint dysfunction in patients with previous pelvic trauma, altered anatomy, and unsuccessful prior surgical intervention. Conclusion: At 18 months of follow-up, she reported over 90% pain relief, along with regained mobility and improved sleep, and no adverse effects were noted. This single case suggests that minimally invasive SI joint fusion, including as a revision procedure, may succeed in complex post-traumatic scenarios where pelvic anatomy has been surgically altered, although these findings cannot be generalized beyond this patient.